Challenges in Post Merger Integration an analysis based on a case study from CEE - Vodák, Martin; Jaklová, Martina L.; Klofanda, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The thesis is covering an analysis of a concrete acquisition case from CEE. Based on the review of theory a conceptual framework was created and then applied to the acquisition case in order to analyze the process of post-merger integration. As a result, recommendations were created for similar future transactions.
Vedoucí práce: Martina L. Jaklová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses